2009
DOI: 10.1111/j.1469-8986.2009.00855.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced cardiac perception is associated with benefits in decision‐making

Abstract: In the present study we provide the first empirical evidence that viscero-sensory feedback from an internal organ is associated with decision-making processes. Participants with accurate vs. poor perception of their heart activity were compared with regard to their performance in the Iowa Gambling Task. During this task, participants have to choose between four card decks. Decks A and B yield high gains and high losses, and if played continuously, result in net loss. In contrast, decks C and D yield small gain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
131
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 158 publications
(145 citation statements)
references
References 51 publications
9
131
1
Order By: Relevance
“…[39][40][41][42] As mentioned above, in previous studies individuals with low levels of cardiac interoceptive awareness performed more poorly on task quantifying attention and executive function. 11,12 Therefore, it appeared worthwhile to examine whether the reduction in interoceptive awareness expected in FMS is associated with cognitive deficits related to this condition. Finally, the impact of comorbid affective and anxiety disorders, and the use of psychoactive medication, on interoceptive awareness was analyzed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[39][40][41][42] As mentioned above, in previous studies individuals with low levels of cardiac interoceptive awareness performed more poorly on task quantifying attention and executive function. 11,12 Therefore, it appeared worthwhile to examine whether the reduction in interoceptive awareness expected in FMS is associated with cognitive deficits related to this condition. Finally, the impact of comorbid affective and anxiety disorders, and the use of psychoactive medication, on interoceptive awareness was analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Outside of the field of emotion, high interoceptive individuals performed better on neuropsychological tasks quantifying basic and higher cognitive functions. 11,12 Additional correlates of accurate interoceptive awareness include a more positive body image, assessed via questionnaires, and reduced proneness to experimentally induced distortions in body scheme. 4,13 In further studies, using questionnaire and experimental methods, high interoceptive individuals demonstrated greater expression of empathy, 14 improved behavioral self-control with respect to physical load, 15 and superior regulation of hunger and satiation compared to low interoceptive individuals.…”
Section: Introductionmentioning
confidence: 99%
“…High heart-focused interoceptive accuracy/sensitivity has been associated with increased emotional intensity [10], has been shown to support memory [11,12] and adaptive decisionmaking [13][14][15], and has predicted increased emotional intensity and reactivity to emotional pictures [16]. 1 Furthermore, it has been suggested that mood and anxiety disorders may root in issues related to interoception [17].…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with previous studies (e.g., Pollatos, Kirsch, & Schandry, 2005;Werner, Jung et al, 2009), we used a cut-off score of ≥.85 to assign participants to the group with high cardiac interoceptive awareness. Participants with a score of < .85 were assigned to the group with regular cardiac interoceptive awareness.…”
Section: Assessment Of Cardiac Interoceptive Awarenessmentioning
confidence: 93%